Evaluation of the 75 s strength endurance test by comparing metabolic and biomechanical values in lab and field - Huber, A.; Goll, M.; Stöcker, F.; Spitzenpfeil, P.; Stauffer, T.; Waibel, K. (Abstractband der 6. Internationalen Konferenz Wissenschaft und Skisport. 14.-19. Dezember 2013, St. Christoph am Arlberg, Österreich, 2013)
Strength endurance is a key factor in conditioning for a successful race performance. Therefore the 75s strength endurance test is one part of the tests of the physical abilities and has been done for the last 12 years on a mechatronic legpress (Desmotronic, Schnell Trainingsgeräte GmbH). The task is to push for 75 seconds at any time at least 60% of the athletes` individual maximum power with both legs in the concentric and eccentric phase. Although there are correlations to the performance in racing, there is one major criticism concerning the fact that in testing there is no recovery between cycles like there is in skiing between turns. The aim of the study, done with the support of the female EC team (N=5; age: 19 years; height: 165.2 ± 2.3 cm, body mass: 65.7 ± 5.8 kg), was to detect similarities and differences in race- like situations and in the 75s test by comparing metabolic and biomechanical values.